What ought to be and political duty: International observations. The case of the 2015 sectional elections in Bolivia - Pacheco Avilez, Raquel (2019)
The analysis of the Bolivian Election Day during the sectional elections of 2015 states the importance of international observations in the studies on democracy within the framework of the political sciences, and constitutes a marker that determines the legitimacy of the process in general. Considering the methodology applied and the perspective that could bring greater value to an international effort with atomizingeffect, this research intends to develop forms of measurement that respond to context logics as an objective contribution to contrast the political perspectives.The contributions obtained from different geographical viewpoints represent an objective opportunity to analyze through comparative politics what works or does not work in the territories. Hence the importance of their independence, transparency and credibility of the outcomes, in order not only to put the observed country in the “defendants’ bench”, but to contribute with genuine democratic exercises that respond to the local reality.